Biological Consequences of the Coaster Brook Trout Restoration Stocking Program in Lake Superior Tributaries within Pictured Rocks National Lakeshore. (21st March 2013) - Leonard, Jill B. K.; Stott, Wendylee; Loope, Delora M.; Kusnierz, Paul C.; Sreenivasan, Ashwin
Abstract: The coaster Brook Trout Salvelinus fontinalis is a Lake Superior ecotype representing intraspecific variation that has been impacted by habitat loss and overfishing. Hatchery strains of Brook Trout derived from populations in Lake Superior were stocked into streams within Pictured Rocks National Lakeshore, Michigan, as part of an effort to rehabilitate adfluvial coaster Brook Trout. Wild and hatchery Brook Trout from three streams (Mosquito River, Hurricane River, and Sevenmile Creek) were examined for movement behavior, size, physiology, and reproductive success. Behavior and size of the stocked fish were similar to those of wild fish, and less than 15% of the stocked, tagged Brook Trout emigrated from the river into which they were stocked. There was little evidence of successful reproduction by stocked Brook Trout. Similar to the results of other studies, our findings suggest that the stocking of nonlocal Brook Trout strains where a local population already exists results in limited natural reproduction and should be avoided, particularly if the mechanisms governing the ecotype of interest are poorly understood. Received April 1, 2012; accepted November 26, 2012